Terephthalic Acid (TPA) Recovery from Plastic Bottle of Polyethylene Terephthalate (PET) through Hydrolysis Treatment. Issue 1 (1st October 2022) - Alias, S; Abdul-Hakim, N A
Abstract: Recovery of plastic waste has a positive influence on solid waste management as it can bring new life to plastic waste. Hydrolysis treatment is one of the approaches for plastic waste recovery, in which plastic monomer can be recovered through depolymerisation. This study explored the recovery of polyethylene terephthalate (PET) plastic in nitric acid and leachate. The weight changes were analysed in PET when exposed to different hydrolysis agents (nitric acid and leachate) at different reaction times and temperatures. The monomer recovery of PET, known as terephthalic acid (TPA), was also evaluated. It was found that high temperatures and reaction times promoted to the high recovery of TPA. The PET residue measured as weight difference was found in line with the trend of TPA yield. The hydrolysis using nitric acid can recover more TPA than the leachate system. The knowledge obtained from this study would be beneficial in upcycling plastic waste into high-value end products.